Perkembangan terapi insulin konvensional hingga insulin analog: Literatur review - Khoirunnisa, Hasna; Kamilah, Putri; Adiyatma, Raditya; Syifa, Salma Nabila; Mufidah, Salwa; Nada, Zakiyyah Qothrun; Ridwan, Heri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The increasing prevalence of diabetes mellitus (DM) globally demands the development of more effective and physiological insulin therapies. Although DNA-engineered conventional human insulin has replaced animal insulin since the 1980s, conventional insulin has drawbacks, such as a pharmacokinetic profile that does not match human physiology, slow absorption, and a higher risk of nocturnal hypoglycemia. Purpose: To comprehensively assess advances in insulin therapy, highlighting key differences in pharmacokinetics, clinical efficacy, and safety between conventional and analog formulations. Method: This study employed a literature review design with a literature search of PubMed, Google Scholar, and OpenAlex databases using the keywords: